2005
DOI: 10.1111/j.1467-9450.2005.00441.x
|View full text |Cite
|
Sign up to set email alerts
|

Decoding, knowledge, and strategies in comprehension of expository text

Abstract: We examined the relative contribution of decoding, topic knowledge, and strategic processing to the comprehension of social science text in a sample of Norwegian junior high school students. Additionally, we examined the interaction of topic knowledge with strategic processing on students' text comprehension, and whether poor word-level skill could be effectively compensated for by higher-level processing involving knowledge or strategies. Multiple regression analysis indicated that students' prior knowledge a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
73
1
9

Year Published

2008
2008
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 75 publications
(90 citation statements)
references
References 49 publications
7
73
1
9
Order By: Relevance
“…In addition, reading comprehension in Grade 4 had a unique effect on knowledge of reading strategies in Grade 5. Previous cross-sectional studies found small to moderate correlations between reading strategies and reading comprehension (e.g., Muijselaar & de Jong, 2015;Samuelstuen & Bråten, 2005). In accordance with these previous studies, we also found moderate relations between knowledge of reading strategies and reading comprehension, in both fourth and fifth grades.…”
Section: Discussionsupporting
confidence: 81%
“…In addition, reading comprehension in Grade 4 had a unique effect on knowledge of reading strategies in Grade 5. Previous cross-sectional studies found small to moderate correlations between reading strategies and reading comprehension (e.g., Muijselaar & de Jong, 2015;Samuelstuen & Bråten, 2005). In accordance with these previous studies, we also found moderate relations between knowledge of reading strategies and reading comprehension, in both fourth and fifth grades.…”
Section: Discussionsupporting
confidence: 81%
“…Presumably, this concentration on accumulating historical facts may be reinforced by teacher beliefs in knowledge and knowing in history as the memorization and reproduction of factual information (cf., VanSledright 2002). At the same time, it should be noted that all elaborative processing is not created equal, and that elaboration may not always be facilitative and sometimes even counterproductive, as when it involves the incorporation of idiosyncratic, irrelevant background knowledge into text representations (Martin and Pressley 1991;Samuelstuen and Bråten 2005;Williams 1993).…”
Section: Prior Research On Strategic Processing Of Multiple Textsmentioning
confidence: 99%
“…One of the prominent NLS scholars, Brian Street (1984), refers to the simple view of reading as an "autonomous model" of literacy, because it relies on the idea that literacy in itself-autonomously-will have specific cognitive effects regardless of the context in which these "skills" are applied. Autonomous models of literacy thus ignore how factors such as prior knowledge and cultural conventions greatly influence our understanding of a text (Norris & Phillips, 1994;Samuelstuen & Bråten, 2005) A social view of literacy, on the other hand, shifts the focus from a set of individual skills or competences to a view of literacy as something you do-a social practice involving text (Barton, 2007). Street (1984) refers to this as an "ideological model" of literacy, because it acknowledges that literacy is always embedded in different cultural and ideological contexts.…”
Section: Sociocultural Perspectives For Researching Literacy In a Schmentioning
confidence: 99%